The Role of Teachers in Shaping the Leadership Characteristics of Madrasah Ibtidaiyyah Nurussalam - Ikhwan Mahmudi; Nada Ni’ma Layalia; Eva Sonia; Rizky Nadia (AL-ASASIYYA: Journal Of Basic Education, 2021)
This study aims to determine the role of the teacher in shaping the leadership characteristics of the students of Madrasah Ibtidayyah Nurussalam. This research uses the type of field research. (field research). With a qualitative descriptive research approach. This research took place in Madrasah Ibtidayyah Nurussalam, Sambirejo, Mantingan, Ngawi, East Java. Data collection methods consist of interviews, observation, and documentation. The results of this study indicate that the teacher's role in shaping the leadership characteristics of the students of Madrasah Ibtidayyah Nurussalam, Sambirejo, Mantingan, Ngawi, East Java, includes: (1) providing good examples; (2) introducing responsibilities, (3) providing direction and motivation; (4) giving group assignments or work, (5) forming an organization, (6) providing approaches and escorts; and (7) providing training, and habituation. In their role in shaping the leadership character of students, teachers face several obstacles caused by internal factors and external factors. Internal factors include, (1) The low level of self-awareness and sensitivity of students to the environment, (2) Lack of confidence, (3) Low discipline. While external factors include: (1) The family environment is not good and (2) the association is not good.